Analisis Klaster dengan Value Chain Analysis : Studi Kasus pada Klaster Mebel Rotan di Surakarta - Susila, Ihwan; Kussudyarsana, Kussudyarsana; Fatchurrohman, Fatchurrohman (Benefit, 2007)
Indonesian cluster studies has been an emerged issue in business studies. This paper studies rattan cluster industry in Surakarta by using value chain analysis proposed by Porter (1985). We use embedded case study methods in order to capture the depth of the issue. The result shows that there are two kinds of procurement in the Surakartarattan cluster, they are cash and credit with unique terms of trade. Also, this study shows that raw material is the main problem in the industry. We recommend that the Indonesian government should pay more attention to the supply of raw material in the rattanindustry.